2016
DOI: 10.18084/1084-7219.21.1.97
|View full text |Cite
|
Sign up to set email alerts
|

LGBT Family Camp as Cultural Immersion for Social Work Students

Abstract: This article presents a model, based on traditional study-abroad programs, for social work students' cultural immersion with local populations. Students who volunteered at an LGBT-parent family camp reported on the impact of the experience in the areas of knowledge about diversity, professional and personal identity, skill development, and managing emotional reactions. Data analysis suggested that learning occurred in all areas identified in the model. BSW students reported increased awareness of the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The author used no formal method of qualitative analysis; however, according to the author, the students reported that the course and its infused policy project gave them a better understanding of course content, various levels of government, and advocacy; made them more marketable; and encouraged them to become involved in various policy activities. Similarly, in a course involving a cultural immersion program, service-learning facilitated an understanding of the link between policy and advocacy (Mercier, Harold, Johnson, & Pond, 2016). Twenty-eight undergraduate social work/pre-social work students over a period of three years participated in a week-long camp for LGBT-parent families.…”
Section: Service-learning In Social Policy Curriculummentioning
confidence: 99%
“…The author used no formal method of qualitative analysis; however, according to the author, the students reported that the course and its infused policy project gave them a better understanding of course content, various levels of government, and advocacy; made them more marketable; and encouraged them to become involved in various policy activities. Similarly, in a course involving a cultural immersion program, service-learning facilitated an understanding of the link between policy and advocacy (Mercier, Harold, Johnson, & Pond, 2016). Twenty-eight undergraduate social work/pre-social work students over a period of three years participated in a week-long camp for LGBT-parent families.…”
Section: Service-learning In Social Policy Curriculummentioning
confidence: 99%